Comparative Evaluation of Methods for Switching Temporary Frequency Support in Islanded Systems - Moraco, Anna G. M.; Grilo, Ahda P.; Otto, Rodrigo B.; Oliveira, Maiara C.; Ramos, Rodrigo A. (IEEE PES Conference On Innovative Smart Grid Technologies Latin America (Online), 2019)
Systems with distributed generators (DG) capable of operating in islanded mode usually present large variations of frequency during the transition from the grid-connected to the islanded operation mode. These variations can be even more critical if the grid presents wind generation. Variable-speed wind generators do not respond intrinsically to frequency variations, and their control should be switched to enable the release of part of its kinetic energy during frequency disturbances. This paper presents an analysis of different switching strategies for temporary frequency support of wind generation based on doubly fed induction generator (DFIG) in the transition to islanded operation. The islanded system considered presents a wind power penetration level of 50% and, under steady-state conditions, the synchronous generation is responsible for the frequency regulation. The results show that, for this situation, the performance of the well-known virtual inertia is improved if this control is switched off when the rate of change of frequency reaches zero for the first time. As a basis of comparison, a second type of control (based on a constant additional power injection) was also tested. This second control, however, was only effective when the system was subject to very large power imbalances.